Análise de crescimento e conversão da energia solar em feijoeiro (Phaseolus vulgaris L) submetido a três níveis de densidade do fluxo radiante - Fernandes Lopes , Nei; Oliva , Marco Antonio; de Freitas , José Guilherme; Melges , Elena; de Macêdo Beltrão , Napoleão Esberard (Revista Ceres, 2025)
Growth analysis and evaluation of solar energy efficiency were carried out with common bean (Phaseolus vulgaris L), variety Negrito 897, under three light levels (30, 62 and 100% of sunlight) in the greenhouse.